Farm to School of Park County : a journey from program to nonprofit, (B) - Cates, Karen L.; Howard, Liz Livingston (London : Kellogg School of Management, 2019)
The second in a four part case series, this case describes Farm to School's decision to enter into a fiscal sponsorship agreement with the local community foundation. The next task for the organization's leaders is recruiting founding board members. The organization must now decide whom to ask and how to do it.
Originally Published In Cates, K. L., & Howard, L. L. (2019). Farm to School of Park County: A Journey from Program to Nonprofit (B). 5-418-751(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nonprofit organizations -- Montana -- Management -- Case studies; Community organization -- Montana -- Case studies